SPATIAL DISTRIBUTION OF HOTSPOTS USING S-NPP VIIRS FOR EARLY DETECTION OF POTENTIAL FIRE - Kumalawati, Rosalina; Dewi, Avela; Yuliarti, Astinana; Anggraini, Rizky Nurita; Murliawan, Karnanto Hendra (GeoEco, 2023)
Fire is a disaster and its frequency is increasing every year. Seeing this, it is very important to know the spatial distribution of hotspots to determine the potential for fires in each area. Based on this, it is necessary to conduct research with the title "Spatial Distribution of Hotspots Using S-NPP VIIRS for Early Detection of Potential Fires". This research includes the type of descriptive research. The population in the study were all hotspots in Banjar Regency, South Kalimantan Province. Hotspots were taken from the results of the S-NPP VIIRS satellite imagery recording from 2012-2021. The number of samples is equal to the number of populations. The data analysis technique uses nearest neighbor analysis and descriptive analysis which is processed using Arc GIS software. The research results show that fires occur during the dry season, namely in July, August, September and October. Spatial distribution of hotspots from the results of S-NPP VIIRS satellite imagery based on the accuracy of the most confidence level in July, August, September and October. If the spatial distribution of hotspots is known, it can be used as an early detection effort. Early detection is carried out as an effort to prevent and control fires with a greater negative impact. In addition, with the existence of an early warning system, the community is better prepared to deal with fires so that the negative impacts that may arise due to fires can be minimized, including loss of life and property.